The Effect of the LKPD-Assisted MIKiR Approach on Improving the Mathematical Critical Thinking of Students in Grade VIII at MTs Negeri 1 Batam - Susilowati, Erlina; Wahyuningrum, Endang; Sukmaningadji, Sandra (Jurnal Sains Sosio Humaniora, 2025)
Academic Year. The sample was taken using a Purposive sampling technique, selected class VIII.3 as the experimental class with a total of 36 students and class VIII.2 as the control class with a total of 28 students. Data were obtained from the mathematical critical thinking ability test instrument on the material finding the formula for the area of a mathematical circle. The results of the analysis show that: (1) The mathematical critical thinking ability of students who received MIKiR approach learning assisted by LKPD is higher than students who received conventional learning, (2) The increase in mathematical critical thinking ability of students who received MIKiR approach learning based on LKPD is higher than students who received conventional learning. The N-Gain index for students who received MIKiR learning with the assistance of student worksheets (LKPD) was 0.7553, categorized as high classification, and 75.53% as effective interpretation.